BRAF V600E mutation in papillary thyroid cancer is correlated with adverse clinicopathological features but not with iodine exposure - (:unkn) unknown (My University, 2019)
INTRODUCTION: BRAFV600E activating mutation is the most frequent genetic abnormality in the pathogenesis of papillary thyroid carcinoma. We aimed to evaluate the association between BRAFV600E mutation and well-established prognostic clinicopathological characteristics as well as iodine exposure. MATERIAL AND METHODS: From 2000 to 2012, the data of PTC patients admitted to Dr. Lutfi Kirdar Kartal Education and Research Hospital in Turkey were reviewed retrospectively. Clinicopathological parameters were collected. BRAFV600E mutation was analysed by DNA sequencing method in tumour specimens. We hypothesised thatBRAFV600E mutation prevalence is positively correlated with prolonged iodine exposure and expected to be higher in the second half of the recruitment period due to the increment in time spent from the iodisation process of the table salt in our country. Thus, iodine exposure was categorised as short-term (2000-2006) and long-term (2006-2012). RESULTS: A total of 197 patients were accrued. The study population predominantly consisted of conventional variant. A statistically significant relationship was observed betweenBRAFV600E mutation presence and age (p = 0.03), conventional variant PTC (p = 0.00002), T4 stage (p = 0.002), vascular invasion (p = 0.036), thyroid capsule invasion (p < 0.00001), extrathyroidal tissue invasion (p < 0.00001), and lymph node metastasis (p < 0.00001). When categorised as long-term and short-term, iodine exposure was not statistically significantly related withBRAFV600E mutation; however, there were far more PTC cases in the long-term group (86.3% vs. 13.7%). CONCLUSION: We revealed that BRAFV600E mutation is associated with adverse clinicopathological parameters. There appeared to be no relation between long-term iodine exposure and BRAFV600E.
Keywords: Adult; Female; Humans; Middle Aged; Male; Proto-Oncogene Proteins B-raf; Thyroid Neoplasms; Neoplasm Invasiveness; DNA Mutational Analysis; Carcinoma, Papillary; Iodine Radioisotopes; BRAF V600E; iodine; papillary thyroid cancer